Portrait of Capital Accounting Practiced by Students of Sharia Accounting Department From Gorontalo Ethnic - Thalib, Mohamad Anwar (UIN Kiai Ageng Muhammad Besari Ponorogo, 2022)
This study aims to reveal the values of local wisdom from the way students majoring in Islamic accounting from the Gorontalo tribe practice capital accounting. This study uses an Islamic paradigm with an Islamic ethnomethodology approach. There are five data analysis stages: charity (amal), knowledge (ilmu), faith (iman), information revelation (informasi wahyu), and good deeds (ihsan). The results showed that before receiving the scholarship, the initial capital to finance college was obtained by students from both their parents and their families. The practice of capital accounting is conditional on the value of local wisdom in the form of responsibility. This value is one of the advice the elders often express through lumadu